Christoph Willibald von Gluck and the Dawn of the Reform of Opera - Karácsony, Noémi (Babes-Bolyai University Cluj-Napoca, 2017)
The aim of this paper is to present the historical, cultural, aesthetic and musical circumstances that led to the gradual unfolding of the reform process of the opera as an art form. The state in which music drama found itself at the beginning of the 18th century contributed to the formulation of essential principles that could guide the composition of a music drama, a work of art which had to transmit true feelings and emotions. The philosophical ideas expressed by the intellectuals of the Enlightenment are echoed in the musical works of Ch. W. von Gluck and mirrored in Orfeo ed Euridice, the unfolding of the reform of opera and the first of Gluck's works in which the composer strives to place the words before the music, relinquishing the old compositional methods.
Keywords: Gluck; Orfeo ed Euridice; reform; principle; opera; declamation